HUBUNGAN JUMLAH UANG BEREDAR DENGAN INDEKS HARGA SAHAM GABUNGAN Dl PASAR MODAL - Syaipan Djambak; Saadah Yuliana; Eny Eny (Jurnal Ekonomi Pembangunan, 2004)
The purpose of this research is to find out the effect on money supply for combination prices indeks in Jakarta Stock Exchange. The sampling period is from 1991 until 2002. Quantitative for analisys are with regression models. The result on regression models is not significant  to predicable money supply influence on the combination prices indeks. In this paper, the writer use the portofolio theory, and money supply  theory. The writer hope this paper can became the resources of information that can explain the influence of money supply to combination price indeks. Keyword· Money Supply, Price Indeks